(3bUjOI aj eOM GdPGJ GdeMeOjI hGdMbjbI GdCMeOjIs - (3GdHcQj, eUWai Hf ceGd GdOjf Hf Ydj, J(B1162(3g`s ((3YHO GdQMef Hf CHG jRjO GdHdjSj GdTGaYjs)
(3ChdgG (B:s
(3jG MVQJ GdbOS Ef GdQH fGOGc (B*** (3jG QhVI GdCfS Ef GdHQ COfGcs
(3BNQgG (B:s
(3Ch eUWai PGJ jS dgG MGcj (B*** (3jG QhVI GdCfS Ef GdHQ COfGcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 239s
(3eYLe GdeDdajf(B: 3 / 876s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs